Peter J Derrick and the Grand Scale 'Magnificent Mass Machine' mass spectrometer at Warwick. Issue 6 (December 2017) - Colburn, AW; Derrick, Peter J; Bowen, Richard D
The value of the Grand Scale 'Magnificent Mass Machine' mass spectrometer in investigating the reactivity of ions in the gas phase is illustrated by a brief analysis of previously unpublished work on metastable ionised n-pentyl methyl ether, which loses predominantly methanol and an ethyl radical, with very minor contributions for elimination of ethane and water. Expulsion of an ethyl radical is interpreted in terms of isomerisation to ionised 3-pentyl methyl ether, via distonic ions and, possibly, an ion-neutral complex comprising ionised ethylcyclopropane and methanol. This explanation is consistent with the closely similar behaviour of the labelled analogues, C3 H7 CH2 CD2 OCH3 +. and C3 H7 CD2 CH2 OCH3 +., and is supported by the greater kinetic energy release associated with loss of ethane from ionised n-propyl methyl ether compared to that starting from directly generated ionised 3-pentyl methyl ether.